Analysis Repair End Voltage and shrink Technical with Reconfiguration Network 20 KV distribution on Feeder PT PLN (Persero) Service Unit Silago Customer (ULP) Sitiung - Pondri, Ferdian; Sukardi, Sukardi (Dinasti Information and Technology, 2023)
There is voltage drop at the tip feeder silago because length network feeder the resulted distribution Genre Power electricity to customer suboptimal . By Because That done analysis transfer burden network with method reconfigure network distribution voltage intermediate feeder the original syllabus is output from substation Connect (GH) Sungai Dareh Then moved to feeder river dareh that direct output from substation Main (GI) Lansek River with use ETAP application 19.01, so expected can repair voltage drop across the feeder sylago so that distribution Genre Power electricity to customer can be optimal.